2007
DOI: 10.1021/ie070373+
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Metal Monolith Catalyst for Natural Gas Steam Reforming

Abstract: Production of hydrogen from natural gas is the most cost-effective and simplest technology for commercial hydrogen generation. Natural gas is also a likely source of hydrogen for residential fuel cell systems, due to its wide availability and ease of conversion via steam methane reforming. Although catalyst technology is available for generating hydrogen from natural gas, the design of new catalysts and new catalytic supports to overcome the limitations associated with ceramic catalyst provides an opportunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Alumina is commonly used as a support but during reforming process the nickel spinel phase (NiAl 2 O 4 ) is generally formed. The formation of the nickel spinel phase could accelerate the deactivation [7]. Supports play an important role in catalytic activity due to chemical effect or interaction between the active phase and the support phase.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina is commonly used as a support but during reforming process the nickel spinel phase (NiAl 2 O 4 ) is generally formed. The formation of the nickel spinel phase could accelerate the deactivation [7]. Supports play an important role in catalytic activity due to chemical effect or interaction between the active phase and the support phase.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of Ni-based catalysts depend on the dispersion of Ni, which is affected on the metal loading and the surface area of the support used [25,26]. It was reported that Ni-based catalysts, can be deactivated easily due to coking and sintering of Ni metal [27], however; this can be solved by optimizing the catalyst contents regarding the Ni loading levels for the selected operation conditions as discussed and studied in the current work. The catalytic methane steam reforming is a surface reaction, thus increasing the amount of active Ni, will increase the surface area, and so the activity the reforming process.…”
Section: Introductionmentioning
confidence: 91%
“…At the beginning of the reaction, the temperature of both the reaction bed and the inlet gases (CH 4 and H 2 O) are at the temperature set by the experiment. (27) Regarding the species conservation, the composition of the species is given in mass fraction terms. At the beginning of the reaction, the gases within the reactor are CH 4 and H 2 O, where the initial conditions have been set for these two species while for the other gases (H 2 , CO 2 and CO) the mass fraction is equal to zero.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…The most commonly used catalysts are nickel-and noble metal-based catalysts (Ru, Rh, Pd, Ir, Pt) [3] [4]. Noble metals present better performances since they are less prone to oxidation, coking and sintering [8], but are more expensive and hence not the preferred option. The main issues with nickel are the deactivation caused by deposition of carbon and/or sintering of metal particles [5] [6].…”
Section: Introductionmentioning
confidence: 99%